UNFAIR TERMS IN CONTRACTS CONCLUDED BETWEEN TRADERS AND CONSUMERS, IN ROMANIAN AND EUROPEAN LAW - VOICULESCU, Ion Cătălin (Journal of Advanced Research in Law and Economics; Vol 3 No 2 (2012): JARLE Volume III, Issue 2(6), Winter 2012, 2017)
The European Union's internal market has the potential to become the largest retail market in the world, but at the moment it is fragmented into 27 markets, hence the market is created within national borders. Technical progress and open e-commerce opportunities are way ahead of consumer behaviour and even the dealer’s. There are still major retainers in purchasing products from another country, not knowing the way your interests as a consumer are protected by the laws of that State. The current market conditions are fundamentally different from those existing at the time of adoption and subsequent transposition of Directive 93/13/EEC. The minimum harmonization proposed by that State has been effective up to a point, but it is obviously not enough. The national regulations raise barriers to the internal market, affecting traders and consumers. The full harmonization of some key regulatory aspects will considerably increase the legal security for both consumers and traders. Both consumers and traders will be able to rely on a single regulatory framework based on clearly defined legal concepts that govern certain aspects of the contracts concluded between traders and consumers in the EU. The effect of such harmonization will eliminate the barriers stemming from the fragmentation of the rules and will create the internal market in this field. These barriers can only be eliminated by establishing uniform rules at the Union level. In addition, consumers will enjoy a high common level of protection across the Union [1] , and the harmonization will be full, the Member States being able to maintain or introduce in their national law, also provisions diverging from those laid down in this Directive, including more or less stringent provisions, to ensure a different level of consumer protection. Unfair terms in consumer contracts represent only a segment in consumer protection field and it is a topic that has recently come to the attention of the public opinion in Romania, together with the consumption credit problem. The media insisted especially on this issue, given a certain degree of novelty, and due to the large number of people affected. The purpose of this approach is not to analyse this problematic sector of credit agreements, but to define some terms used by the Romanian legislation and analyse a relevant case law of the Court of Justice of the European Union, on the interpretation of the rules of Council Directive 93/13/EEC of 5 April 1993 on unfair terms in consumer contracts and how relationships between consumers and traders will be affected that as an effect of the adoption this year of the new Directive on consumer’s protection.   [1] Position of the European Parliament adopted at first reading on June 23 2011 to the adoption of Directive 2011/83/ EU of the European Parliament and Council on consumer rights, amending the Council Directive 93/13/EEC and Directive 1999/44/EC of the European Parliament and Council and revoking the Council Directive 85/577/EEC and Directive 97/7/EC of the European Parliament and Council, available at www.europarl.europa.eu .